Legionella pneumophila occurrence in drinking water supplied by private wells. (24th January 2020) - Mapili, K.; Pieper, K. J.; Dai, D.; Pruden, A.; Edwards, M. A.; Tang, M.; Rhoads, W. J.
Abstract: Unregulated private wells are understudied potential sources of community‐acquired Legionnaires' disease. Here we conducted a comprehensive survey of 44 homes supplied by private wells in Wake County, North Carolina, quantifying Legionella spp. DNA, Legionella pneumophila DNA, and total bacterial 16S rRNA genes via real‐time polymerase chain reaction in hot and cold drinking water samples, along with culturable L. pneumophila via IDEXX Legiolert in cold drinking water samples. Legionella spp. DNA, L. pneumophila DNA and culturable L. pneumophila were detected in 100, 65·5 and 15·9% of the 44 homes, respectively, and culturable levels were comparable to some municipal surveys applying the same methods. Total coliforms and Escherichia coli were monitored as representative faecal indicators and were found in 20·4 and 0·0% of homes. Within certain sample types, Legionella spp. and L. pneumophila gene copy numbers were positively associated with total bacteria (i.e. total 16S rRNA genes) and water softener use, but were not associated with faecal indicator bacteria, inorganic water parameters or other well characteristics. These findings confirm that occurrence of Legionella and L. pneumophila is highly variable in private wells. Significance and Impact of the Study: Legionella is the leading identified cause of waterborne disease outbreaks associated with US municipal water systems. While Legionella is known to occur naturally in groundwater, prior efforts to characterize its occurrence in unregulated private wells are limited to sampling at the wellhead and not in the home plumbing where Legionella can thrive. This work documents much higher levels of Legionella in home plumbing versus water directly from private wells and examines factors associated with higher Legionella occurrence. Abstract : Significance and Impact of the Study: Legionella is the leading identified cause of waterborne disease outbreaks associated with US municipal water systems. While Legionella is known to occur naturally in groundwater, prior efforts to characterize its occurrence in unregulated private wells are limited to sampling at the wellhead and not in the home plumbing where Legionella can thrive. This work documents much higher levels of Legionella in home plumbing versus water directly from private wells and examines factors associated with higher Legionella occurrence.